CALIBRATION TEST RESULT ACCELEROMETER SENSOR - Quart Ferrina; Sri Ratna Sulistiyanti; Junaidi Junaidi (Jurnal Teori dan Aplikasi Fisika, 2022)
Abstract. MEMS sensors commonly used in various studies for cost efficiency in production and well produced in large quantities. Sensor calibrate was important because of large quantities product and ensure that product can be operate proper and the output based on standard production. The ADXL345 sensor calibration test is carried out by measuring the output acceleration on a combination of 3 axes X, Y, and Z, named X+ (X axis gets a positive gravitational acceleration of 1 g), X (X axis gets a negative gravitational acceleration of 1 g), Y+, Y - , Z+, and Z-. A total of 100 data were collected and 10 data were presented in tables in each condition and presented in graphical form. ZeroG offset testing on the X-axis and Y-axis is carried out in the Z+ condition because in this condition the X-axis and Y-axis get a natural acceleration of Earth's gravity of 0 g. In this condition, the acceleration value on the Z axis is 0.9074g . For the X axis is -0.0048 g and -0.0778 g for the Y axis. This value is obtained from the average acceleration value of the X axis and Y axis in the Z+ condition. The zeroG offset test on the Z axis is determined by taking the middle value of the average measurement results in the Z+ and Z- conditions. This value is not the same as the typical value in the datasheet of 0 g, but the 0g offset value of these three axes is still within the minimum range of the sensor datasheet. The sensitivity value of the sensor in the calibration test results has a tendency to differ on each axis. The X-axis of 4.0012 mg/LSB maximum range, Y-axis of 3.9900 mg/LSB close to the values on the data sheet, and Z-axis of 3.7403 mg/LSB near the range of values